Obstetric Concern, Management and Considerations in the Context of COVID-19 Pandemic - Haque, Nadira; Hosain, Nazmul; Ara, Gulshan; Nasrin, Begum; Fatema, Nargis; Dorjey, Yeshey (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Coronavirus disease (COVID-19) has emerged as a global threat. The disease largely attacks adults with higher mortality among the aged and compromised people. Although previous coronavirus havocs caused significant number of maternal and neonatal demise, most pregnant cases with COVID-19 infection are either asymptomatic or with mild symptoms only. This pandemic brought significant disruption of essential antenatal and intranatal care worldwide. The health resources became diverted to focus on general population needs rather than the specified needs of pregnant women. Limited information is known about the effect of COVID-19 disease on pregnancy. Recent evidence indicates that pregnant women are not vulnerable group for severe COVID-19 illness. However, immunological and physiological alterations during pregnancy expose women more vulnerable to SARS-CoV- 2 infection in comparison to general population.Covid-19 pandemic has created a global crisis causing great challenges for pregnant women and their obstetricians. Although the due course of pregnancy is not strained by the disease itself but complications can happen in absence of proper care and caution. Both the pregnant mother and care-giver should be vigilant and the obstetric management should be implemented following evidence based standard protocol. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 49-56